"I Wanna Be in the Room Where It Happens"…: Using Curriculum Mapping to Support the Information Literacy Goals of Online Programs. Issue 1 (3rd April 2019) - Ziegler, Amanda
Abstract: Embedding information literacy and instruction within an online program can be a difficult process to begin. Curriculum mapping guides librarians to the courses where their services can have the most impact. However, curriculum mapping can seem like an overwhelming and unwieldly process. This case study demystifies the process and shows how simple and effective curriculum maps can be designed and utilized. Particularly in environment with a single librarian dedicated to online outreach serving as a coordinator for other subject liaison librarians, curriculum mapping is a tool that allows for clear communication, outreach and systematic assessment. This paper will provide an overview of how the curriculum maps were developed, how they were used for communication and outreach both within and outside the Libraries, and ideas for programmatic assessment based upon the maps.